2007
DOI: 10.1128/cvi.00184-07
|View full text |Cite
|
Sign up to set email alerts
|

Functional Antibodies to the O-Acetylated Pneumococcal Serotype 15B Capsular Polysaccharide Have Low Cross-Reactivities with Serotype 15C

Abstract: The 23-valent pneumococcal polysaccharide (Ps) vaccine offer protection against vaccine serotypes, but its cross-protection against vaccine-related serotypes is variable. We have demonstrated that the functional antibodies to serotype 15B are specific to the O-acetylated 15B-Ps and that they have low cross-reactivity with serotype 15C. Demonstration of functionally cross-reactive antibodies to vaccine-related serotypes is important for surveillance and vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Perhaps the most important unstable modification may be O-acetylation. Knowledge of O-acetylation is important because O-acetyl groups can contribute to the conformation of PS and are often antigenic targets (epitopes) (e.g., serotypes 15B/C, 11A, and others [44]). Yet, O-acetyl groups can be easily lost and variably expressed, and therefore it can be quite difficult to assign the location and degree of O-acetylation exactly.…”
Section: Biochemical Elucidation Of Capsular Diversitymentioning
confidence: 99%
“…Perhaps the most important unstable modification may be O-acetylation. Knowledge of O-acetylation is important because O-acetyl groups can contribute to the conformation of PS and are often antigenic targets (epitopes) (e.g., serotypes 15B/C, 11A, and others [44]). Yet, O-acetyl groups can be easily lost and variably expressed, and therefore it can be quite difficult to assign the location and degree of O-acetylation exactly.…”
Section: Biochemical Elucidation Of Capsular Diversitymentioning
confidence: 99%
“…Serotypes 1 and 5, which were the most resistant to C3 opsonization and opsonophagocytosis, have a smaller number of available targets (-OH or -NH 2 groups) for C3b to make ester or amide linkages. The importance of acetyl groups to the antigenicity of pneumococcal polysaccharides was reported in a previous study in which the functional activity of antibodies was evaluated using an opsonophagocytic assay (41). It was shown that the target of vaccine induced antibodies was linked to an Oacetyl group present in the monosaccharide residues of serotype 15B and that these antibodies were not cross-reactive against serotype 15C, whose capsular polysaccharide is otherwise identical but not acetylated (41).…”
Section: Vol 78 2010mentioning
confidence: 99%
“…One common variation is O-acetylation, which can alter both immune recognition and capsular physicochemical properties. Pneumococcal and meningococcal vaccine trials found that O-acetyl groups can be targets of vaccine-elicited antibodies and suggested that O-acetylation could be necessary for a successful vaccine response (8,9). O-acetylation is also important for innate immune recognition.…”
mentioning
confidence: 99%